2017
DOI: 10.1016/j.nmd.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Early onset facioscapulohumeral dystrophy – a systematic review using individual patient data

Abstract: Infantile or early onset is estimated to occur in around 10% of all facioscapulohumeral dystrophy (FSHD) patients. Although small series of early onset FSHD patients have been reported, comprehensive data on the clinical phenotype is missing. We performed a systematic literature search on the clinical features of early onset FSHD comprising a total of 43 articles with individual data on 227 patients. Additional data from four cohorts was provided by the authors. Mean age at reporting was 18.8 years, and 40% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 68 publications
(74 reference statements)
2
56
0
Order By: Relevance
“…For example, only two of our patients were non‐ambulant, with another nine having severely limited mobility. Given the likelihood of further deterioration over the next few years, this is in keeping with a recent literature review that identified that 40% of patients with early‐onset FSHD were wheelchair‐dependent by 18 years . Similarly, it is likely that both our incidence and our intervention rates for scoliosis are misleadingly low, as the younger children in our cohort may yet develop spinal complications.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…For example, only two of our patients were non‐ambulant, with another nine having severely limited mobility. Given the likelihood of further deterioration over the next few years, this is in keeping with a recent literature review that identified that 40% of patients with early‐onset FSHD were wheelchair‐dependent by 18 years . Similarly, it is likely that both our incidence and our intervention rates for scoliosis are misleadingly low, as the younger children in our cohort may yet develop spinal complications.…”
Section: Discussionsupporting
confidence: 78%
“…Given the likelihood of further deterioration over the next few years, this is in keeping with a recent literature review that identified that 40% of patients with early-onset FSHD were wheelchair-dependent by 18 years. 16 Similarly, it is likely that both our incidence and our intervention rates for scoliosis are misleadingly low, as the younger children in our cohort may yet develop spinal complications. Similarly again, the prevalence of significant pain in our group (11/18) is in keeping with the results of a survey of adult patients in which 82% reported pain.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, whereas the frequency of de novo mutations tends to be higher in early‐onset FSHD (73%42), our cohort showed a lower frequency (14% in the whole group, 22% in the early‐onset subgroup), which is more in line with classic onset FSHD with de novo mutations in up to 30%43). A correlation between disease severity and the repeat size, as found in earlier research,44 was not demonstrated in this cohort.…”
Section: Discussionmentioning
confidence: 40%
“…Patients with very large contractions typically have earlier onset and more severe disease with faster progression. Earlier age at onset of facial weakness in patients with early onset FSHD (symptoms occurring within the first 10 years of life) has been associated with greater disease severity [48,49]. Men have been reported as more severely affected than women [19,50], although this was not observed in a study assessing patients with early disease onset [48].…”
Section: Disease Progressionmentioning
confidence: 96%